Quantification of Educational Inequality through the Application of Gini Coefficient in Educational Indices - SATOSHI WATARAI; SAKI TOMITA (Journal of Advanced Research in Social Sciences and Humanities, 2017)
Aim: This paper aims to show why it is important to keep an eye on educational disparities across countries and how to do so.Methodology: The paper uses the Gini coefficient of education, a method suggested by Hojo (2009) and Thomas, Wang, and Fan (2001). The degree of inequality in educational attainment was measured using this technique, and its historical development in Japan, Korea, and the United States was followed. Then, the Gini index was contrasted with the mean years people spend in school to see how the two measures evolved over time.Findings: The results showed that while educational inequality increased at varying rates across the three countries, the mean number of years people spent in school rose steadily. Second, it discovered that the Gini coefficient of Korea and the United States differed significantly, even though both countries have a sizable population that is highly educated.Novelty/Implications: This is a rare paper because it not only makes a case for why it’s important to pay attention to educational inequality but also explains what it is and how it relates to a more standard measure of educational achievement. In addition, the Gini coefficient was evaluated through a series of comparisons with other results.